2019
DOI: 10.1111/os.12566
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes and Prognostic Factors of Myxoid Liposarcoma in Extremities: A Retrospective Study

Abstract: ObjectivesTo evaluate treatments and prognostic factors for the myxoid liposarcoma in extremities.MethodsWe retrospectively reviewed 34 patients histologically diagnosed with myxoid liposarcoma arising in the extremities, treated in our hospital from 2010 to 2017. We recorded tumor locations, max diameter, operations, complications, radiation, chemotherapy, survival, recrudescence, and metastases. Overall survival, treatments, and prognostic factors were subsequently analyzed.ResultsThe mean age of 34 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
(38 reference statements)
2
18
0
Order By: Relevance
“…Locoregional metastatic myxoid liposarcoma treatment data are extracted from SEER during 1975-2016, including surgery, radiotherapy, and chemotherapy modalities. Most of the reported cases in the SEER of locoregional metastatic patients with myxoid liposarcoma were performed surgery which is almost 95.2% of the total number of patients, and this result was similar as in the literature [ 38 ]. Radiotherapy treatments of patients with locoregional myxoid liposarcoma of data obtained from SEER showed no big difference between received beam radiations versus unreceived patients, almost 47.1% versus 52.9%.…”
Section: Resultssupporting
confidence: 79%
“…Locoregional metastatic myxoid liposarcoma treatment data are extracted from SEER during 1975-2016, including surgery, radiotherapy, and chemotherapy modalities. Most of the reported cases in the SEER of locoregional metastatic patients with myxoid liposarcoma were performed surgery which is almost 95.2% of the total number of patients, and this result was similar as in the literature [ 38 ]. Radiotherapy treatments of patients with locoregional myxoid liposarcoma of data obtained from SEER showed no big difference between received beam radiations versus unreceived patients, almost 47.1% versus 52.9%.…”
Section: Resultssupporting
confidence: 79%
“…As a consequence of their favorable response to treatment, myxoid liposarcomas have a good prognosis 1 . However, tumor size, positive surgical margins, and local recurrence are all associated with lower rates of disease‐free survival and overall survival 51‐53 . Our case highlights the role of a patient's medical history when evaluating thyroid nodules to optimize accurate diagnosis, as liposarcomas do not typically present in the thyroid gland.…”
Section: Discussionmentioning
confidence: 90%
“…Orson et al ( 33 ) and Reitan et al ( 34 ) both demonstrated that larger tumors were associated with poorer prognosis. Moreover, four larger studies ( 7 , 15 , 18 , 20 ) assessed several prognostic factors for MLPS with varying results. One study showed that tumors >5 cm were associated with worse DSS compared with those <5 cm ( 17 ).…”
Section: Prognostic Factors Of Mlpsmentioning
confidence: 99%
“…Surgical resection remains the first-line treatment for almost all cases of STS, including primary MLPS of the extremities, with the exception of some diffusely metastatic conditions ( 7 , 47 , 48 ). Historically, amputation was once considered the standard therapy to attain local control in patients with extremity STS ( 49 ).…”
Section: Surgical Treatment In Mlpsmentioning
confidence: 99%
See 1 more Smart Citation